The divided diplomat: Ralph Bunche and the contradictions of liberal order - Mampilly, Zachariah (Foreign Affairs)
In September 1948, Folke Bernadotte, the Swedish count serving as the UN mediator for Palestine, was shot dead on the streets of Jerusalem by the Stern Gang, a Zionist terror outfit. His American deputy, Ralph Bunche, was quickly named as his replacement. Over the next 11 months, Bunche, who had planned to be in Bernadotte$1 (Bs motorcade that fateful day but was absent because of a delayed flight, painstakingly negotiated an armistice between the belligerents. It was a brilliant achievement. He returned to a ticker-tape parade in New York City, and the mayor of Los Angeles declared July 17 (3z(BRalph Bunche Day.(3y (BIn 1950,- Reproduced s